Small Intestine Protection of Mica Against Non-Steroidal Anti-Inflammatory Drugs-Injury Through ERK1/2 Signal Pathway in Rats - Zhang, Shuo; He, Yinghua; Shi, Zheng; Jiang, Jianping; He, Beihui; Xu, Sumei; Fang, Zhengyu (Frontiers in Pharmacology, 2019)
Objective: The impact of non-steroidal anti-inflammatory drugs (NSAIDs) to damage the small intestine has been well known. Mica, one kind of natural clay, has been widely marketed in China for the treatment of gastric diseases. However, the role and mechanism of mica in small intestinal injure is still unknown. The study was designed to declare the effects of mica on intestinal injury induced by diclofenac in rats. Methods: Rats were randomly divided into control, model, PAR-2 agonist group (SLIGRL-NH2 group), PAR-2 antagonist group (LRGILS-NH2 group) and ERK blocker group. Morphological changes of mucous membrane of small intestine were observed and the expression of tryptase, PAR-2 and p-ERK1/2 was measured by immunohistochemistry and western blot. PAR-2 mRNA was tested by qRT-PCR. Rats were also randomly divided into control, model and mica group. Morphological changes of mucous membrane were observed. The expression of tryptase, PAR-2 and p-ERK1/2 were measured by immunohistochemistry. Results: The expression of trypsin, PAR-2 and p-ERK1/2 was increased in model and SLIGRL-NH2 group compared with control, and was down-regulated in LRGILS-NH2 and ERK blocker group compared with model. Macroscopically visible lesions of mucous membrane had positive correlation with the expression of trypsin, PAR-2 and p-ERK1/2 and were inhibited by blocking PAR-2 and ERK1/2. Furthermore, we also found that mica could inhibit small intestinal injure, as evidence by the improvement of macroscopic damage. Tryptase, PAR-2 and p-ERK1/2 expression was down-regulation in mica group compared with model group. Conclusion: Mica inhibit small intestinal injure induced by NSAIDs via PAR-2/ERK signaling pathway.